COVID-19 presenting as Acute abdomen- a study of 3 cases - Paul, Shrebash; Islam, Md Khairul; Hasan Chowdhury, Forhad Uddin; Chowdhury, Fazle Rabbi (Journal of Bangladesh College of Physicians and Surgeons, 2023)
COVID-19 is a multisystem disease and sometimes patient can present with life threatening extra-pulmonary manifestations. Amongst GI symptoms nausea, vomiting, abdominal pain and diarrhoea are common. Severe hepatobiliary manifestations like acute pancreatitis, acute hepatitis and cholecystitis are rare in SARS-CoV-2 infection. In this case series we described three cases presented with hepatobiliary manifestations. All of them had acute abdominal pain and finally proven to be the case of acute pancreatitis and acalculous cholecystitis in addition to classical COVID- 19 symptoms. Two of them had severe symptoms and required high volume of oxygen, while one case (acalculous cholecystitis) had mild symptom only. All of them recovered successfully. High degree of clinical suspicion is required while managing atypical presentation of COVID-19 cases. This is also vital to refer the cases to advance care hospitals in time to ensure multidisciplinary care. J Bangladesh Coll Phys Surg 2023; 41(4): 320-324